PERAN BIAS PERILAKU DALAM MEMEDIASI PENGARUH FAKOR DEMOGRAFI, LITERASI KEUANGAN, DAN PENDAPATAN TERHADAP KEPUTUSAN INVESTASI PADA INVESTOR SAHAM SULAWESI TENGGARA - Frieddelia Wathilda Muhaling; Sujono Sujono; Ibnu Hajar; Buyung Sarita; Samdin Samdin; Valentinus Amstrong TN; Zaluddin Zaluddin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
The purpose of this research istest and explaininfluence 1)demographics of investment decisions 2) influence demographics to financial behavior bias 3) influence financial literacy on investment decisions 4) influence of financial literacy on financial behavior bias 5) influence of income factors on financial behavior bias 6) influence of income factors on investment decisions 7)influencefinancial behavior bias towards investment decisions 8) demographic influence on investment decisions mediated by financial behavior bias 9) the effect of financial literacy on investment decisions mediated by financial behavior bias. 10) the influence of the income factor on investment decisions which is mediated by financial behavior bias. The research design used is quantitative research. The data used are secondary data. Data analysis usessoftware Smart PLS.  The results showed that: 1).Demographicsdoes not have a significant effect on investment decisions. 2).Demographics have a significant effect on financial behavior bias.3) Financial literacy has a significant effect on investment decisions. 4) Financial literacy has a significant effect on bias in financial behavior. 5)Income does not have a significant effect on investment decisions. 6) Income has a significant effect on investment decisions. 7) Financial behavior bias has a significant effect on investment decisions. 8)Financial behavior bias is able to mediate (full mediation) the influence of demographics on investment decisions.9). Financial behavior bias is able to mediate (full mediation) the effect of financial literacy on investment decisions. 10)Financial behavior bias is able to mediate (full mediation) the effect of income on investment decisions.